Stakeholders' perceptions, reforms and consequences : report on the First National Forum of SAPRI, Bangladesh - Structural Adjustment Participatory Review Initiative, Bangladesh (Network). National Forum 1998 : Dhaka, Bangladesh); Bhattacharya, Debapriya; Titumir, Rashed A. M. (Dhaka : Shraban Prokashoni, 2001)
Contributed articles presented at the Forum with reference to balance of payments status of Bangladesh.
"Structural Adjustment Participatory Review Initiative (SAPRI), Bangladesh."
Includes bibliographical references (p. 113-114).
Keywords: World Bank; Balance of payments -- Bangladesh; Structural adjustment (Economic policy) -- Bangladesh; Debts, External -- Bangladesh